JavaScript and DOM games course for beginners - Svekis, Laurence (Manning Publications, 2022)
Modify the Document Object Model (DOM) with JavaScript to make your web pages come to life! The DOM is an object-oriented representation of the web page which can be modified with JavaScript to create interactive and dynamic web content. Create a dynamic and interactive game that detects element collision and adds to the score. Move your element to hit the other elements on the page, score, and see how new elements are created with a maximum number from the code. Learn basic JavaScript game structure that can be extended to build your own games and more.
Online resource; title from title details screen (O'Reilly, viewed January 24, 2023)
Keywords: Video games -- Juvenile literature -- Programming; JavaScript (Computer program language) -- Juvenile literature; Document Object Model (Web site development technology); Jeux vidéo; Programmation; Ouvrages pour la jeunesse; JavaScript (Langage de programmation); Ouvrages pour la jeunesse; Modèle DOM (Technologie de développement de sites Web); Video games; Programming; JavaScript (Computer program language); Instructional films; Internet videos; Juvenile works; Nonfiction films; Films de formation; Films autres que de fiction; Vidéos sur Internet